การเปรียบเทียบการเปลี่ยนแปลงระดับแอนติบอดี ในผู้ป่วยก่อนและหลังการรักษาโรคพยาธิตัวจี๊ดระหว่างยาอัลเบนดาโซลและยาไอเวอร์เมกติน - มัทนียา ภัทรธีรฉัตร (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objective of this study were to compare the changing of antibody level by ELISA and the changing of specific antibody by Western Blot, in serum of cutaneous gnathostomiasis patients between pre and post - treatment with albendazole in 14 patients and ivermectin in 15 patients. By ELISA technique, checkerboard titration of antigen and conjugate was performed against pooled positive and negative sera. The cut - off value was the mean + 1SD of those of healthy control sera. All sera which pre and post - treatment for 14 days, 30 days, 60 days, 90 days, 120 days and 1 year with albendazole in 14 patients and ivermectin in 15 patients gave ELISA value above the mean (+1SD) of normal controls, which was arbitrarily used as a cut-off point. There were no significant difference in ELISA OD (p>0.05) in both groups. Sera from 2 groups were studied by sodium dodecyl sulphate - polyacrylamide gel electrophoresis (SDS - PAGE) and Western Blot analysis for specific antigen of G.spinigerum with a MW. of 24 kDa. The cutaneous gnathostomiasis 3 of 14 patients who received albendazole and 1 of 15 patients who received ivermectin were seronegative after treatment. We concluded that there were no different in changing of antibody level by ELISA but changing of specific antibody by Western Blot but there was no statically significant difference.